The Role of Influencers and Digital Marketing in Boosting Sales for Culinary MSMEs in Solo - Anggun Mutiara Utami; Wahyudi, Tri Nur (Jurnal Manajemen Bisnis, 2024)
This study aims to explore the impact of influencers on promoting MSMEs in Solo City, the effectiveness of influencer and digital marketing strategies in supporting MSMEs, and the benefits derived from influencer collaborations. Qualitative research employing a case study approach is utilized, with data validity ensured through source triangulation. Data analysis follows Miles and Huberman's methodology, encompassing four stages: data collection, data reduction, data presentation, and conclusion. The study focuses on MSMEs in Solo City employing influencer marketing strategies, with participants including both influencers and MSME owners. Findings reveal that influencers play a crucial role in introducing MSME products, enhancing brand image and awareness, and significantly boosting sales by up to 2 to 3 times. Moreover, digital marketing, particularly leveraging Instagram as a promotional platform, is highlighted as an effective tool for reaching a wider audience and driving sales growth for Solo's culinary MSMEs.